The evolution of physical attributes of the basketball players from the student team of the chinese university, through the lens of functional training - Yuy Tszyun; Makeeva V.S.; Chernov S.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to empirically validate the enhancement of the physical abilities of the male basketball players from the Chinese university team through the implementation of functional training. Methods and structure of the study. In the course of the research, the physical attributes, agility, reaction time, and stamina of 15 male basketball players from the Heihe University team were assessed. A tailored training regimen was devised. The participants engaged in a 14-week program, with daily workouts lasting approximately 90 minutes. For a comparative evaluation of physical parameters, a group of 49 basketball players from the Division I of the Chinese Student Basketball Association (CUBA) in the 2022-2023 season was selected. Results and conclusions. Following the functional training, the players of Heihe University’s men’s basketball team demonstrated substantial improvements in their strength capabilities (<0,001), speed attributes (<0,001), and endurance (<0,001), indicating the effectiveness of the training program. Functional training is a crucial component in the development of specific physical attributes for basketball players. It has a positive impact on enhancing the flexibility and stability of the upper body, improving statokinetic functions, developing explosive power, maintaining a low center of gravity, and facilitating rapid acceleration, technical adjustments, and endurance.